Anterior Urethral Valves: Not Such a Benign Condition… - Cruz-Diaz, Omar; Salomon, Anahi; Rosenberg, Eran; Moldes, Juan M.; de Badiola, Francisco; Labbie, Andrew S.; Gosalbez, Rafael; Castellan, Miguel A. (Frontiers in Pediatrics, 2013)
Purpose: Anterior urethral valves (AUVs) is an unusual cause of congenital obstruction of the male urethra, being 15–30 times less common than posterior urethral valves (PUVs). It has been suggested that patients with congenital anterior urethral obstruction have a better prognosis than those with PUV, with less hydronephrosis, and a lower incidence of chronic renal insufficiency (5 vs. 30%). The long-term prognosis of AUVs is not clear in the literature. In this report we describe our experience and long-term follow up of patients with anterior urethral valve. Materials and Methods: We retrospectively identified 13 patients who presented with the diagnosis of AUVs in our institutions between January 1994 and June 2012. Two patients were excluded: one patient had no follow up after intervention; the other had a follow up <1 year. From the 11 patients included, we evaluated the gestational age, prenatal and postnatal ultrasound findings, voiding cystourethrogram findings, age upon valve ablation, micturition pattern, creatinine, and clinical follow up. Results: Between 1994 and 2012 we evaluated 150 patients with the diagnosis of urethral valves. Of this group, 11 patients (7.3%) had AUVs and an adequate follow up. Mean follow up is 6.3 years (2.5–12 years). Five (45.4%) patients had prenatal diagnosis of AUV. The most common prenatal ultrasonographic finding was bilateral hydronephrosis and distended bladder. One patient showed a large perineal cystic mass, which was confirmed to be a dilated anterior urethra. The mean gestational age was 37.6 weeks (27–40 WGA). Postnatally, 90% had trabeculated bladder, 80% hydronephrosis, and 40% renal dysplasia. The most common clinical presentation was urinary tract infection in five patients (45.4%), followed by weak urinary stream found in four patients (36.3%). The age at initial surgical intervention ranged between 7 days and 13 years. Seven (63.6%) patients had primary transurethral valve resection or laser ablation and three patients (27.2%) had primary vesicostomies. One boy (9.1%) had penile urethrostomy with excision of urethral diverticulum. Two (18.2%) patients developed end-stage renal disease. Conclusion: Anterior urethral valve is a rare congenital entity affecting the genitourinary system in males. Early urinary tract obstruction resulted in end-stage renal disease in 18% of our patient population. In our series, the complication rate and the evolution to renal failure are high and similar to patients with PUV. In patients with AUVs we recommend long-term follow up and close evaluation of patient’s bladder and renal function.